Design and comparison of two maize seeders coupled with an agricultural robot - López-Gómez, Jesús A.; Patiño-Espejel, Joshua E.; Velázquez-López, Noé; Sánchez-Chávez, David I.; Van Loon, Jelle (MDPI, 2024)
In recent years, the development of robotic vehicles in agriculture has made it possible to reduce human intervention and fatigue in carrying out arduous or repetitive tasks, as well as helping to promote sustainable agriculture to address climate change. However, the great diversity of agricultural tasks and the varied production systems and crops demand a wide range of solutions that can be adapted to robotic vehicles as a power source. These alternatives must be affordable and user-friendly for some users, although more sophisticated solutions must also be developed for others, depending on their specific needs. For this, the present work focuses on the development of two maize seeders with different metering systems coupled to an agricultural robot. The first seeder has a conventional mechanically driven seed metering system with a drive wheel and chain gear, while the second one has an electronically driven metering system based on a DC motor and a digital encoder controlled by a microcontroller. Both seeders were coupled to a remote-controlled robotic vehicle and evaluated on real farmland. Seed distribution in the seed rows was contrasting; the results indicated that the mechanical system performed better in the field than the electronic system. For both seeders, the working capacity was approximately 0.135 ha/h at an average speed of 2.0 km/h. The proposed robot–seeder assembly could help farmers automate and reduce the workload associated with planting, as well as attract young people to the field.